2011
DOI: 10.1039/c1cp20428a
|View full text |Cite
|
Sign up to set email alerts
|

On molecular chirality within naturally occurring secondary organic aerosol particles from the central Amazon Basin

Abstract: In this perspectives article, we reflect upon the existence of chirality in atmospheric aerosol particles. We then show that organic particles collected at a field site in the central Amazon Basin under pristine background conditions during the wet and dry seasons consist of chiral secondary organic material. We show how the chiral response from the aerosol particles can be imaged directly without the need for sample dissolution, solvent extraction, or sample preconcentration. By comparing the chiral-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 72 publications
(87 reference statements)
0
33
0
Order By: Relevance
“…Measuring the phase relationship of the spectral features in the amide and N‐H bands may provide detailed information on the peptide or protein folding structures. Recently, chiral SFG‐VS has been applied to measure and understand protein and DNA structures at the interface or in the membrane, as well as the chirality of small molecules in the natural secondary organic aerosols from tropical and boreal forests . Such understandings and experimental approaches, as shown in this report, shall certainly help to characterize and to understand the structure and interactions of molecular interfaces and biological membranes.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Measuring the phase relationship of the spectral features in the amide and N‐H bands may provide detailed information on the peptide or protein folding structures. Recently, chiral SFG‐VS has been applied to measure and understand protein and DNA structures at the interface or in the membrane, as well as the chirality of small molecules in the natural secondary organic aerosols from tropical and boreal forests . Such understandings and experimental approaches, as shown in this report, shall certainly help to characterize and to understand the structure and interactions of molecular interfaces and biological membranes.…”
Section: Resultsmentioning
confidence: 80%
“…Our interest in the limonene molecules is not only because it has been a benchmark choice for studying molecular chirality with various chiroptical and spectroscopic techniques in the bulk, 10,15,[33][34][35][36] but also because of the importance of a class of chiral isoprene and monoterpene molecules, such as limonene and pinene, etc., in the global secondary organic aerosol (SOA) formation and impact on climate changes. [37][38][39][40][41][42] It has been shown that chirality is not only an important component in the SOA, 39,40 the surface structure and reactivity of these SOA particles are also crucial for understanding the transformation and impact of the SOAs. 41,43 We will show that the nearly identical achiral SFG spectra of R-(+)-limonene and S-(-)-limonene, as well as the RS racemic mixture (50/50 equal amount mixture) suggest that the corresponding molecular groups in the R and S enantiomers are with the same interfacial orientations with respect to the interface normal.…”
Section: Introductionmentioning
confidence: 99%
“…The SML and the surfaces of aerosols have been shown to contain chiral molecules, including lipids, 109 but these are almost always assumed to be biotic in origin. 14,26,27 However, as demonstrated here, it is possible to make chiral molecules in high yields from very simple, achiral precursors, suggesting that the potential for abiotic environmental sources of chirality should not be discounted.…”
Section: Resultsmentioning
confidence: 99%
“…Although nonlinear optics had been applied to nano-and microparticles before, 153−158 the application of SFG to study atmospheric aerosol particles had not been presented prior to 2011, when our first reports on the subject appeared. 92,159,160 Some considerations regarding SFG signal generation from organic aerosol particles in the micrometer and submicrometer range are given in section IXA.…”
Section: Vibrational Sum Frequency Generation (Sfg) Spectroscopymentioning
confidence: 99%